Tindak Pidana Penganiayaan tidak tepat Sasaran dalam Perspektif Pasal 351 ayat (2) Kitab Undang-Undang Hukum Pidana dan Hukum Pidana Islam (Analisis Putusan Majelis Hakim Pengadilan Negeri Bangkalan Nomor 431/pid.b/2018/pn bkl) - R Arif Muljohadi; Abdul Wahid (Jurnal Keislaman, 2020)
The main problem in this research is regarding a persecution committed by the perpetrator as a result of being driven by emotions due to things that are not yet clear, so that what he has done results in harm to other people who do not have any problems with him. So it can be concluded that the perpetrator has committed a maltreatment on purpose but not on target.This type of research uses the library research method (Library Research), which is a technique by conducting an inventory of statutory regulations and documents, also using literature obtained from the decision of the Panel of Judges which has permanent legal force based on the decision of the Panel of Judges at the Bangkalan District Court Number: 431 / Pid.B / 2018.PN Bkl.The results of this study indicate that the technique of the criminal act of persecution either intentionally or unintentionally is an act that is prohibited in Islam. who later will get sanctions, while the sanctions obtained by the perpetrators of this criminal offense of persecution is the law of qishāsh as explained in the Nash Al-Qur'an, so that the substitute punishment for it is diyat or ta'zir. However, when viewed from the applicable law in Indonesia, the perpetrator is subject to imprisonment and a fine in accordance with Article 351 of the Criminal Code concerning maltreatment. Judging from the decision of the Panel of Judges Number 431 / Pid.B / 2018 / PN Bkl that the perpetrator is subject to imprisonment for 1 (one) year and 5 (five) months imprisonment and a case fee of Rp. 2000., (two thousand rupiah).